162 The clinical management of relatives of young sudden arrhythmic death victims; icds are rarely indicated. (9th June 2011) - Caldwell, J C; Borbas, Z; Moreton, N; Khan, N; Kerzin-Storrar, L; Metcalfe, K; Newman, W; Garratt, C J
Abstract : Introduction: Following National Service Framework guidance on the management of sudden cardiac death (SCD), regional inherited cardiac conditions clinics were established to identify and treat those at increased risk of dying from an arrhythmic condition. Studies have examined the yield of different diagnostic strategies but the outcome of management in these patients has not been reported. Methods: We present data on 193 consecutive patients (108 families) referred to a regional inherited cardiac conditions clinic because of SCD/aborted cardiac arrest of a relative. The mean age on referral was 38±17 yrs and mean duration of follow-up was 15 months (range 1 day to 56 months). All individuals underwent clinical assessment by history, examination, ECG and echo. If treadmill exercise test had not previously been performed this was undertaken. Further imaging by CMR or contrast echo was performed in those with structurally abnormal hearts or with T wave inversion in V2 /V3 . Ajmaline provocative testing was performed in those with a history and/or ECG suggestive of Brugada syndrome. Results: Of the 193 patients, 43 individuals (22%) from 36 families (33%) were diagnosed with an inheritable cause of SCD and 145 patients were clinically normal (see Abstract 162 table 1). Five patients were found to have other conditions (LV non-compaction, AVNRT, skeletal myopathy, mild AS and congenital sub-aortic membrane). Of the 43 patients diagnosed with an inheritable condition, 21 had medication commenced by the clinic (β-blockers(21), ACEi/ARB(2), Spironolactone[1]). ICDs were implanted as per HRUK guidelines, resulting in 4 patients having an ICD inserted on clinic recommendation (2 HCM, 1 DCM, 1 ARVC). To date no appropriate therapies have been administered (follow-up 8–29 months) but there was 1 inappropriate shock from a fractured lead. Three individuals had β-blockade withdrawn after negative genetic testing for an established familial mutations (2 CPVT, 1 LQT), one ICD was removed and one deactivated (both negative for CPVT). Of the 145 patients thought to be clinically normal, 85 were reassured and discharged, 13 failed to return to clinic and 47 are regular reviewed as the risk of developing an inheritable condition cannot be excluded; this includes those with family histories of HCM (7), ARVC (12), DCM (9), CPVT (5), Brugada (4) and LQT(1). To date no deaths have occurred in those diagnosed with inherited causes of SCD (follow-up mean 20, 1–52 range) or those clinically normal with ongoing review (follow-up mean 22 months, 1–56 range). Conclusion: A diagnosis of an inheritable cause of SCD was obtained in 22% of individuals and 33% families with a history of SCD/aborted cardiac arrest in a relative. The number of ICDs inserted was very small (2%) and there have been no appropriate therapies in this group. Two ICDs have been removed/deactivated after exclusion of a known familial mutation.